Vitamin D nuclear receptor deficiency promotes cholestatic liver injury by disruption of biliary epithelial cell junctions in mice. Issue 4 (6th September 2013) - Firrincieli, Delphine; Zúñiga, Silvia; Rey, Colette; Wendum, Dominique; Lasnier, Elisabeth; Rainteau, Dominique; Braescu, Thomas; Falguières, Thomas; Boissan, Mathieu; Cadoret, Axelle; Housset, Chantal; Chignard, Nicolas
<x xml:space="preserve">Abstract</x> Alterations in apical junctional complexes (AJCs) have been reported in genetic or acquired biliary diseases. The vitamin D nuclear receptor (VDR), predominantly expressed in biliary epithelial cells in the liver, has been shown to regulate AJCs. The aim of our study was thus to investigate the role of VDR in the maintenance of bile duct integrity in mice challenged with biliary‐type liver injury. Vdr−/− mice subjected to bile duct ligation (BDL) displayed increased liver damage compared to wildtype BDL mice. Adaptation to cholestasis, ascertained by expression of genes involved in bile acid metabolism and tissue repair, was limited in Vdr−/− BDL mice. Furthermore, evaluation of Vdr−/− BDL mouse liver tissue sections indicated altered E‐cadherin staining associated with increased bile duct rupture. Total liver protein analysis revealed that a truncated form of E‐cadherin was present in higher amounts in Vdr−/− mice subjected to BDL compared to wildtype BDL mice. Truncated E‐cadherin was also associated with loss of cell adhesion in biliary epithelial cells silenced for VDR. In these cells, E‐cadherin cleavage occurred together with calpain 1 activation and was prevented by the silencing of calpain 1. Furthermore, VDR deficiency led to the activation of the epidermal growth factor receptor (EGFR) pathway, while EGFR activation by EGF induced both calpain 1 activation and E‐cadherin cleavage in these cells. Finally, truncation of E‐cadherin was blunted when EGFR signaling was inhibited in VDR‐silenced cells. Conclusion: Biliary‐type liver injury is exacerbated in Vdr−/− mice by limited adaptive response and increased bile duct rupture. These results indicate that loss of VDR restricts the adaptation to cholestasis and diminishes bile duct integrity in the setting of biliary‐type liver injury. (Hepatology 2013;58:1401–1412)